Ranger perceptions of, and engagement with, monitoring of elephant poaching. Issue 1 (20th October 2020) - Kuiper, Timothy; Massé, Francis; Ngwenya, Nobesuthu A.; Kavhu, Blessing; Mandisodza‐Chikerema, Roseline L.; Milner‐Gulland, Eleanor J.
Abstract: Ranger‐based monitoring has enormous potential to inform conservation globally, with hundreds of thousands of rangers patrolling extensive areas and recording observations of illegal activities and biodiversity. Much quantitative research has demonstrated the pitfalls and potential of data collection by rangers, but little work has considered its human dimensions. Yet poor engagement with, and ownership of, monitoring by those undertaking it may compromise data quality and thereby limit evidence‐based conservation. We interviewed rangers and supervisors involved in a programme for monitoring and managing elephant poaching in the Zambezi Valley, Zimbabwe. We assess the importance that rangers ascribed to data collection within their broader occupation, and their level of engagement with data management and use. We found that rangers saw the collection of biodiversity data as a routine duty that helped guide patrol strategy. Reporting these data was perceived as a primary way of demonstrating fulfilled responsibilities to their supervisors. Rangers did not, however, engage actively with data management and use. Ranger sentiment was evenly divided between those who said feedback on how the data they collected were used would motivate more engaged data collection, and those who said they would continue collecting data regardless, out of duty. Three elements of the occupational culture of rangers at our site—a strong sense of duty, deference to authority and knowing their defined responsibilities within the organizational hierarchy—were identified as key drivers of their engagement with monitoring. Building on these findings, we develop a theory of change to develop more meaningful engagement of rangers with monitoring. We argue that more effective and sustainable monitoring can be achieved by building on existing ranger culture while also fostering rangers' appreciation of data collection and utilization. Addressing key challenges around ranger well‐being, and resource and capacity needs, is also essential. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.